AI-powered language generators in vocational final examinations – information and discussion urgently needed! - Schürger, Barbara [Verfasser] (My University, 2023)
"Since its release in November 2022, the use of ChatGPT has been gaining popularity. The general consensus is that AI-powered language generators are also expected to impact work and education. Experts discuss their intentional use and/or misuse in exams primarily in the general education and university sector. But what about examinations in vocational education and training? This article analyses the points of contact between the software and VET examination instruments and discusses possible future developments." (author's abstract; BIBB-Doku)
Keywords: L 7 Prüfungen; G 2.2.1 Technologisierung; 370; Berufsbildung; Prüfung; Abschlussprüfung; Künstliche Intelligenz; Einflussfaktor